Pemberdayaan Dan Peningkatan Ekonomi Masyarakat Melalui Ide Dan Inovasi Baru Produk Dari Bahan Dasar Purun Untuk Ibu-Ibu Di Kampung Purun Kelurahan Palm Banjarbaru - Mohammad Zainul; Periyadi Periyadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Palm Village is one of the areas in Palam District, Banjarbaru City, South Kalimantan Province which can be reached by land about 5 km from the Kalimantan Islamic University MAB Banjarbaru. The source of livelihood for the villagers is in the field of handicrafts. Purun is a type of wild plant that grows in swamps. Purun is found in many swamp areas in South Kalimantan. In the dry season, purun is very flammable and causes a lot of smoke which is detrimental to health, traffic and even flights. Purun can be processed into a variety of interesting woven crafts such as mats, sandals, handbags and so on. One of the villages that is a center for purun crafts is Palam Village. The people of Palam Village have been familiar with crafts from this purun material for generations, which are generally made into mats with various motif.